Efektivitas intervensi teen anger management and education dalam mengatasi masalah kemarahan dan agresivitas pada remaja perempuan - Claudya Carolina; Mita Aswanti Tjakrawiralaksana (Jurnal Ilmiah Psikologi Terapan, 2021)
Anger management based on the cognitive-behavioral approach is considered an effective intervention to treat anger and aggressivity in adolescence. This study investigates the effectiveness of the cognitive-behavioral intervention on anger in female middle-high school students in Depok. Eight female adolescents (age 12-14) were recruited to participate in this intervention using the purposive sampling method. Anger level was measured during the pre-test, post-test, and follow-up phases using a self-report questionnaire and a program evaluation sheet. Wilcoxon-Sign Rank test showed no significant difference in the participants’ anger level between the three measurement phases. However, according to the program evaluation, the result shows that the participants applied new strategiesto deal with their anger and aggressive behavior. Statistically, the cognitive-behavioral intervention was not effective for treating anger in female adolescents. However, participants were reported to use more adaptive strategies in managing their anger. This intervention could be applied for overcoming aggression and anger in female adolescents in the future.